Pembuatan Video Edukasi Permohonan Perubahan Daya Listrik melalui Aplikasi PLN Mobile Menggunakan CapCut pada PLN ULP Kebonagung - Nur Laila Purwanto; Joni Dwi Pribadi; Tri Ramadani Arjo; Fatkhur Rochman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to create an educational video on the procedure for applying for a change in electric power through the PLN Mobile application using CapCut and to measure its effectiveness as a customer information medium at PLN ULP Kebonagung. The study employed the Action Research method with Kurt Lewin's model, consisting of planning, action, observation, and reflection stages. Data were collected through observation, interviews, questionnaires, and documentation. The video's effectiveness was measured using the Technology Acceptance Model (TAM) with five indicators: Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, Behavioral Intention to Use, and Actual Usage. The research respondents consisted of 15 people, including PLN customers, the ULP Kebonagung manager, multimedia experts, and marketing experts. The results showed that the educational video achieved an overall percentage of 95.91%, categorized as highly effective. All TAM indicators showed highly effective results, with Actual Usage achieving the highest percentage (97.78%). The educational video was considered capable of helping customers understand the procedure for applying for a change in electric power more easily, clearly, and systematically. Therefore, this educational video is worthy of being used as a digital information medium by PLN ULP Kebonagung to enhance understanding and encourage the utilization of the PLN Mobile application in electric power change services.